2008
DOI: 10.1007/s00464-008-9850-y
|View full text |Cite
|
Sign up to set email alerts
|

The malignant adenoma: when to operate and when to watch

Abstract: The dilemma as to which course of action is in the best interest of the patient with high-risk adenoma, be it either therapeutic polypectomy alone or surgical resection, is best resolved by a multidisciplinary team involving the surgeon, pathologist and endoscopist, taking the patient's condition and wishes into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…There is no clear description of the CT/MR FU for this whole group. In contrast with most other publications in the literature [2,3] this study could not establish a link between lymphovascular invasion and the presence of residual tumour or lymph node metastasis. The authors, in the discussion section, warned against discounting the importance of these features but it is noteworthy that patients with ASA grades 3 and 4 were more likely to have surgery, despite being the very patients for whom endoscopic resection would be beneficial.…”
contrasting
confidence: 99%
“…There is no clear description of the CT/MR FU for this whole group. In contrast with most other publications in the literature [2,3] this study could not establish a link between lymphovascular invasion and the presence of residual tumour or lymph node metastasis. The authors, in the discussion section, warned against discounting the importance of these features but it is noteworthy that patients with ASA grades 3 and 4 were more likely to have surgery, despite being the very patients for whom endoscopic resection would be beneficial.…”
contrasting
confidence: 99%
“…The result of a study, which was recently conducted by Seit et al [21] on 114 patients who had undergone an endoscopic polypectomy of a malignant polyp, showed that poor outcomes were obtained from 60 high-risk patients due to the relevant malignant tumor whereas good outcomes were obtained from 54 low-risk patients regardless of the tumor. They suggested that a more active treatment should be conducted if risk factors are identified during the pathohistologic examination [21, 25]. In this study, surgery was performed on the patients that were considered to have risk factors on the histologic examination after the polypectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred care for patients with polypectomy specimens which contain invasive carcinoma is controversial (Haboubi and Scott, 2000). Taking into considerations all factors involved, the issue of polypectomy for malignant polyps versus surgical resection is best resolved by a multidisciplinary team involving the surgeon, pathologist and endoscopist, taking the patient's condition and wishes into account (Mitchell and Haboubi, 2008).…”
Section: Resultsmentioning
confidence: 99%